Simulation-Based Application for Improving Drinking Water Production Process: A Case Study of The Drinking Water Factory in Chanthaburi - Mhoraksa, Thiti; Samattapapong, Nara; Yunyao, Supakit; Wongsakul, Pongsathon (RMUTL Engineering Journal, 2020)
The objective of this research was to apply simulation techniques to reduce production time of the gallon drinking water production process due to the highest time production. The water production process which currently takes 26,966.34 seconds per 400 gallon or takes 67.42 seconds per gallon was studied. It was found that there was a problem with bottleneck during the water filling process. Therefore, three scenarios were generated to solve the problem then each scenario was tested using experimenting tool through simulation analysis process. The simulation model of the gallon drinking water production process was created using Flexsim® simulation software. The results showed that the scenario which added 1 employee and added water filling machine was the optimal solution for increasing efficiency in the production process. By this scenario, the average production time was reduced to 17,093.80 seconds per 400 gallon or 42.73 seconds per gallon. The reduced production time was 9,873.54 seconds or 2 hours 44 minutes or the average of reduced production time was 24.68 seconds per gallon which was equivalent to 36.61%